Forensic Accounting and Fraud Prevention in Nigerian Public Sector: A Conceptual Paper - S., Abdulrahman, (International Journal of Accounting & Finance Review, 2019)
This study examines forensic accounting and fraud prevention in Nigerian public sector by using some selected studies from within and outside Nigeria. The objectives of the study are to determine how does forensic accounting prevents fraud in Nigeria Public Sector and to determine whether forensic accounting prevents fraud in Nigeria Public Sector. To achieve the stated objectives of the study, data were collected from secondary source or Content Analysis. Based on the analysis, the study found that a significant positive influence exists between forensic accounting techniques and fraud prevention. The paper is of the opinion that more steps should be taken to ensure fraud prevention with the application of forensic accounting techniques. Moreover, an effective and thorough legal framework should be developed and be provided for effective enforcement of what the law say by government agencies that were saddled with such responsibility on behalf of the government.